Basic Statistics for Economists. - Kovtun, Natalia (Cambridge Scholars Publisher, 2022)
This book presents a detailed consideration of the methodological principles and the main methodological techniques of statistical research. It covers the history of the conception of statistics, a statistical observation, tabulating and grouping, the analysis of distribution rows, the sampling method, the analysis of dynamic rows, the index method, and the statistical study of interconnections. As such, the book illustrates the conditions and peculiarities of the use of statistical methods, and will help the reader interpret the results of their studies properly. It will appeal to students of.